Bilayer-Structured Regenerated Cellulose/Chitosan Films Prepared with Ionic Liquid - Faisal Amri Tanjung; Yalun Arifin; Abdul Hamid Abdullah; Iqmal Tahir (Indonesian Journal of Chemistry, 2017)
The effects of chitosan on properties of regenerated cellulose/chitosan (RC/Ch) films were investigated. The films were prepared using a sequence process of solution-casting in a lithium chloride/N,N-dimethylacetamide ionic liquid, and coagulation in water. Due to the amorphous structure of chitosan and the formation of hydrogen bonding between the functional groups of the both components, tensile strength of the films decreased considerably; however, elongation at break increased. Furthermore, SEM morphology indicated a visible separated layers comprising of rigid and ductile surfaces. The addition of chitosan clearly improved the thermal stability of the films, although the thermal degradation mechanism was not altered.